Rotating Arm-Based Experimental Study on Droplet Behavior in the Shoulder Region of an Aircraft Aerodynamic Surface - S. Sor; A. García-Magariño; A. Velazquez (International Journal of Aerospace Engineering)
An experimental study has been performed on water droplet deformation in the shoulder region of an airfoil. The experiments have been carried out in a rotating arm facility 2.2 m long and able to rotate up to 400 rpm (90 m/s). A blunt airfoil model (chord length equal to 0.468 m) was placed at the end of the arm. A droplet generator was used to generate a stream of water droplets with an initial diameter of 1000 μm. An imaging system was set up to record the trajectories and deformations of the droplets in three different regions close to the airfoil shoulder. The base flow field was characterized using a particle image velocimetry system. The experiments show that droplet deformation results in the shoulder region of the airfoil are different from those pertaining to the leading edge region. In particular, droplets in the shoulder region tend to rotate to the direction of the incoming airfoil which generates an interference effect between the droplets that make up the stream. These differences have been quantified applying an existing theoretical model specifically developed for the leading edge region to the results obtained in the present study.